2014
DOI: 10.1007/s11606-014-2843-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Targeted and Tailored Patient Depression Engagement Interventions on Patient–Physician Discussion of Suicidal Thoughts: A Randomized Control Trial

Abstract: Exposure of patients with at least moderate depressive symptoms to an individually tailored intervention designed to increase patient engagement in depression care led to increased PCP discussion of suicidal thoughts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For example, advances in information technology could be used in connection with automated practice audits (Almeida et al., 2012 ) and for the facilitation of client-provider communication and decision-making (Duberstein & Wittink, 2015 ). A recent intervention study demonstrated increased clinician inquiry about suicide when older adults completed a brief computerized survey in the waiting room (Shah et al., 2014 ). More research is needed on whether eliciting and responding to older adults’ psychological needs in the context of medical care reduces the risk of suicidal behaviour and improves other health outcomes (Duberstein & Wittink, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, advances in information technology could be used in connection with automated practice audits (Almeida et al., 2012 ) and for the facilitation of client-provider communication and decision-making (Duberstein & Wittink, 2015 ). A recent intervention study demonstrated increased clinician inquiry about suicide when older adults completed a brief computerized survey in the waiting room (Shah et al., 2014 ). More research is needed on whether eliciting and responding to older adults’ psychological needs in the context of medical care reduces the risk of suicidal behaviour and improves other health outcomes (Duberstein & Wittink, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This project recognises patient, family and caregiver engagement as a key health system improvement strategy. Research has found evidence of impacts of engagement on healthcare services 20 and patient outcomes, 21 22 as well as benefits of engagement for participants. 23 Nonetheless, there is a recognition of a need for a greater understanding of the theoretical underpinnings of engagement 20 and of the best methods by which engagement can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that having patients complete a brief (median use time 5 min) interactive multimedia computer program (IMCP) while waiting to see their doctor led to increased clinician inquiry about suicidal thoughts, without disturbing workflow. 15 Rather than simply informing patients that they are symptomatic, the individually tailored IMCP was designed to activate patients with suggestive symptoms to consider the possibility that they might be depressed, and to motivate them to raise discussion of depression during the linked visit, thereby "opening the door" for the providers to inquire about suicide. One likely advantage of tailored IMCPs over simple "screening" is less vulnerablility to focalism bias, the diversion of patient and clinician attention from relevant contextual issues.…”
Section: Optimistic Humanism Engineeredmentioning
confidence: 99%